Electronic Information Resources Utilisation by Student of Rhema University Library - Ogbuagu, Ozioma Prudent; Ezenwa, Ezinne Nkechinyere; Osedo, Onyinye Alexander; Arisukwu, Felicia Eberechi (Communicate: Journal of Library and Information Science, 2023)
The paper examined the Electronic Information Resources Utilisation by Students of Rhema University Library. The study highlights the various electronic resources utilised by the students, challenges in the utilisation of electronic information resources and the strategies that can be adopted to enhance proper utilisation of electronic information resources. The study adopted a descriptive survey design. The population of the study comprised of all registered student users of Rhema University library. Instruments deployed for data collection were availability check list and questionnaire. Data collected was analysed using frequency counts, simple percentage and mean value. Findings revealed that Rhema students are conversant with, and utilise, the following electronic information resources: e- journal, e-book, e- manuscripts. E-map, Online Public Access Catalogue (OPAC), e-magazine, e- thesis, e-bibliographic database and Web Online Public Access Catalogue (WebOPAC), whereas e- reference, e- research report, electronic mails, e-data archives and CD-ROM were not utilised. The study observed that Lack of ICT skills, difficulty in locating EIRs, frequency of systems breakdown, as challenges of e-resources utilisation. The study recommended that Rhema University Library management should ensure frequent maintenance of computer systems, recruitment of librarians with skills on deployment and management of electronic information resources among other things with conclusion that searching strategies for EIRs be included in university curriculum..